Cellular operator network monitoring and optimization system structure development - Одарченко, Р. С. (Science-based technologies, 2017)
In the work it is determined that high requirements to the quality of service provision, operative connection of new subscribers and expansion of the network place principally new tasks for the continuous assessment of network usage indicators for its optimization, reconfiguration, expansion, definition of tariff policy. To ensure the operation of this system an appropriate model was developed on the basis of which the algorithm of work was developed. The subscriber's prototype application for the Android operating system, which allows the subscriber to handle IoT devices, has been developed to assess key service quality indicators. A number of system benefits were also identified.